Efficiency and integration in european banking markets - Ferreira, Cândida (2011)
This paper seeks to contribute to the relatively scarce published research on the relationship between bank efficiency and European integration in the wake of the recent financial crisis. Using Stochastic Frontier Analysis and Data Envelopment Analysis approaches, the study estimates bank efficiency for different panels of European Union countries during the time period 1994-2008. The main conclusions point to the persistence of inefficiencies, which decreased with the implementation of the European Monetary Union (in the time period 2000-2008) but then increased slightly in the most recent phase (2004-2008), during which the EU had to adapt to the new universe of 27 member-states. On the other hand, there is evidence of a convergence process, although this is very slow and not strong enough to avoid the differences in the country efficiency scores.